Composite electrode material, positive electrode, supercapacitor and preparation method
By coating nano zinc sulfide and nano nickel sulfide on the foam nickel matrix to form a composite electrode material with a bishell structure, the problem of poor cyclic stability of transition metal sulfide materials is solved, and the energy storage and cycling performance of supercapacitors is significantly improved.
Patent Information
- Application Number
- CN202210393001.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-04-14
AI Technical Summary
The existing transition metal sulfide materials have large volume changes during charging and discharging, resulting in poor cycle stability, limiting their application in supercapacitors.
Using a foam nickel matrix as the core, the thin sheet nano zinc sulfide and cube or cubic nano nickel sulfide are coated through electrochemical deposition technology to form a composite electrode material with a bi-shell structure.
The electronic conductivity and stability of the composite electrode material are improved, energy storage performance and cycle stability are enhanced, and the specific capacitance is achieved with a capacity retention rate of up to 1903.2F/g and a capacity retention rate of 500 cycles is up to 81.4%.
Smart Images

Figure CN114843110B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical materials, and in particular to a composite electrode material, a positive electrode, a supercapacitor and a preparation method thereof. Background Art
[0002] In order to solve the problems of energy shortage and environmental pollution, environmentally friendly and sustainable new energy sources have attracted much attention, and the development of high-performance, low-cost energy storage devices has become a hot topic in current research. Among the many energy storage devices, supercapacitors are favored by researchers due to their advantages such as fast charging and discharging efficiency, ultra-high power density and green environmental protection. They have a wide range of applications in power systems, industrial control, transportation, aerospace and other fields. This green and environmentally friendly energy storage device has replaced many other ordinary electrochemical energy storage devices and has very promising application prospects in real life.
[0003] In recent years, transition metal sulfides have attracted widespread attention due to their abundant reserves, low cost, environmental friendliness and high theoretical specific capacity. They are widely used in various fields such as semiconductor materials, electrode materials, and magnetic materials. However, metal sulfides have poor cycle stability due to their large volume changes during the charge and discharge process, which seriously limits their application in supercapacitors. Therefore, the development of an electrode material with large specific capacitance and high stability is of great significance to the development of supercapacitors. Summary of the invention
[0004] In view of the problem that existing transition metal sulfide materials have low specific capacitance and poor cycle performance, which seriously limit their application in supercapacitors, the present invention provides a composite electrode material, a positive electrode, a supercapacitor and a preparation method.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] A composite electrode material comprises a foamed nickel matrix, thin-sheet nano zinc sulfide coated on the outside of the foamed nickel matrix, and rectangular or cubic nano nickel sulfide coated on the outside of the nano zinc sulfide.
[0007] Compared with the prior art, the composite electrode material provided by the present invention has thin-sheet nano zinc sulfide coated on the outside of nickel foam, and there are long and thin gaps between the large-sheet nano zinc sulfide. Such gaps are beneficial to increasing the contact between zinc sulfide and the electrolyte and providing a good electron transport channel for electron transfer. At the same time, the thin-sheet structure will not significantly increase the resistance of the composite electrode material, and is beneficial to alleviating the volume effect during the charge and discharge process, thereby facilitating the improvement of the electronic conductivity and stability of the composite electrode material; the cubic or rectangular nickel sulfide coated on the outside of the thin-sheet zinc sulfide can, on the one hand, further increase the effective specific surface area of the electrode material, shorten the ion diffusion distance and the electron transmission path, thereby enhancing the energy storage performance of the composite electrode material; on the other hand, the presence of the outer layer of nickel sulfide can also slow down the volume expansion of the inner layer of zinc sulfide during the reaction process, thereby enhancing the cycle stability of the composite electrode material.
[0008] The present invention also provides a method for preparing a composite electrode material, comprising the following steps:
[0009] Step a, using nickel foam as an anode and a cathode, respectively, to perform electrodeposition in a zinc sulfide electrodeposition solution, washing, drying, and obtaining a zinc sulfide / nickel foam electrode material at the cathode; wherein the deposition potential is -0.4V to 1.3V, and the scanning rate is 780mV / s to 820mV / s;
[0010] Step b, using nickel foam as an anode and the zinc sulfide / nickel foam electrode material as a cathode, performing electrodeposition in a nickel sulfide electrodeposition solution, washing, and drying to obtain a nickel sulfide@zinc sulfide / nickel foam composite electrode material at the cathode; wherein the deposition potential is -0.4V to 1.3V, and the scanning rate is 780mV / s to 820mV / s.
[0011] The present invention prepares a double-shell-coated nickel sulfide@zinc sulfide / nickel foam composite electrode material by sequentially electrochemically depositing zinc sulfide and nickel sulfide on a nickel foam substrate under specific conditions. The unique morphology and structure and the synergistic effect of zinc sulfide and nickel sulfide significantly improve the electronic conductivity, ion diffusion rate, chemical stability, and electrochemical activity, reduce the activation energy of electron transfer between metal centers, and increase the active sites of the composite electrode material in the electrochemical reaction, thereby significantly enhancing the energy storage performance and cycle stability performance.
[0012] The present invention significantly improves the specific capacity and stability of the composite electrode material through the coordinated regulation of morphology and composition. At a current density of 19 A / g, the specific capacitance can reach 1903.2 F / g, the capacity retention rate after 500 cycles can reach 81.4%, the capacity retention rate after 1000 cycles can reach 71.7%, and the capacity retention rate after 5000 cycles can still reach 51.6%. The energy storage performance and cycle performance are excellent, and a superior composite electrode material is provided for supercapacitors. The preparation method has a wide range of raw material sources, low price, simple and easy preparation process, high preparation efficiency, can be mass-produced, and has broad application prospects.
[0013] Optionally, the nickel foam needs to be pretreated before electrochemical deposition to remove impurities on the surface of the nickel foam.
[0014] Furthermore, the nickel foam is cut into small pieces and then added to acetone and hydrochloric acid solutions for ultrasonic treatment for 15-20 minutes, and then ultrasonically treated with deionized water for 10-20 minutes to obtain a clean nickel foam matrix.
[0015] Preferably, the zinc sulfide electrodeposition solution is a mixed aqueous solution of a soluble zinc salt and thiourea, wherein the concentration of the soluble zinc salt is 5 mmol / L to 20 mmol / L, and the concentration of the thiourea is 0.4 mol / L to 0.6 mol / L.
[0016] Furthermore, the soluble zinc salt is zinc chloride or zinc nitrate.
[0017] Preferably, the nickel sulfide electrodeposition solution is a mixed aqueous solution of a soluble nickel salt and thiourea, wherein the concentration of the soluble nickel salt is 0.1 mmol / L to 0.4 mmol / L, and the concentration of the thiourea is 0.7 mol / L to 1.3 mol / L.
[0018] Furthermore, the soluble nickel salt is nickel chloride or nickel nitrate.
[0019] Preferably, in step a, the electrodeposition time is 12 min to 30 min.
[0020] Preferably, in step b, the electrodeposition time is 12 min to 30 min.
[0021] The preferred concentration of the electrodeposition solution and the electrodeposition time are conducive to obtaining a flaky nano zinc sulfide structure and a cubic or rectangular nano nickel oxide structure, and the nano nickel oxide is uniformly coated with the nano zinc oxide to form a typical double shell structure, and is conducive to making the ratio of zinc sulfide to nickel sulfide appropriate, improving the synergistic effect of zinc sulfide and nickel sulfide, and combining with the unique morphology structure, greatly increasing the energy storage performance and chemical stability of the composite electrode material.
[0022] The present invention also provides a composite electrode material, which is prepared by any of the above-mentioned methods for preparing the composite electrode material.
[0023] The present invention also provides a positive electrode, comprising the above composite electrode material.
[0024] The present invention also provides a supercapacitor, comprising the above-mentioned positive electrode.
[0025] The composite electrode material prepared by the present invention has excellent cycle stability and energy storage performance. The composite electrode material is applied to supercapacitors to obtain supercapacitors with stable structure and excellent specific capacity, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD diagram of the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 of the present invention, wherein (A) nickel foam, (B) nickel sulfide@zinc sulfide / nickel foam composite electrode material;
[0027] Figure 2 This is a scanning electron microscope image of the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 of the present invention, wherein: Figure 2 (A) is blank nickel foam, Figure 2 (B) is zinc sulfide / nickel foam electrode material, Figure 2 (C) is a nickel sulfide@zinc sulfide / nickel foam composite electrode material;
[0028] Figure 3 This is the XPS graph of the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 of the present invention, wherein: Figure 3 (A) is Ni3S2 / nickel foam, Figure 3 (B) is Ni 2p , Figure 3 (C) is S 2p ;
[0029] Figure 4 The constant current charge-discharge curves of the nickel sulfide @ zinc sulfide / nickel foam composite electrode material prepared in Example 1 of the present invention at different mass current densities, wherein, from left to right according to the direction of the arrows, they are: 50A / g, 25A / g, 24A / g, 23A / g, 22A / g, 21A / g, 20A / g, 19A / g;
[0030] Figure 5 The constant current charge-discharge curves of the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 of the present invention at different area current densities, wherein the arrow direction from left to right is: 20 mA / cm 2 , 10mA / cm 2, 9mA / cm 2 , 8mA / cm 2 , 7mA / cm 2 , 6mA / cm 2 , 5mA / cm 2 ;
[0031] Figure 6 The linear graphs obtained by fitting the cyclic voltammetry curves of the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 at different scan rates, wherein (a) 0.2V, (b) 0.4V;
[0032] Figure 7 This is a distribution diagram of the proportion of surface control and diffusion control in the chemical reaction of the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 at different scanning rates;
[0033] Figure 8 This is a cycle retention rate diagram of the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1;
[0034] Fig. 9 This is a SEM image of the zinc sulfide / nickel foam electrode material prepared in Comparative Example 1;
[0035] Fig.10 The constant current charge-discharge curves of the nickel sulfide / zinc sulfide / nickel foam electrode material prepared in Comparative Example 1 at different mass current densities, wherein the arrows from left to right are: 60A / g, 20A / g, 15A / g, 14A / g, 13A / g, 12A / g;
[0036] Fig.11 The constant current charge-discharge curves of the nickel sulfide / zinc sulfide / nickel foam electrode materials prepared in Example 1 and Comparative Example 2 at different area current densities, wherein: Fig.11 (A) is Example 1, and the arrow direction from left to right is: 20mA / cm 2 , 10mA / cm 2 , 9mA / cm 2 , 8mA / cm 2 , 7mA / cm 2 , 6mA / cm 2 , 5mA / cm 2 ; Fig.11 (B) is comparative example 1, and the arrow direction from left to right is: 20mA / cm 2 , 10mA / cm 2 , 9mA / cm 2 , 8mA / cm 2 , 7mA / cm 2 , 6mA / cm 2 ;
[0037] Fig.12 This is a SEM image of the zinc sulfide / nickel sulfide / nickel foam composite electrode material prepared in Comparative Example 3;
[0038] Fig.13 The constant current charge and discharge curves of the zinc sulfide / nickel sulfide / nickel foam composite electrode material prepared in Comparative Example 3 at different mass current densities, wherein the arrows from left to right are: 60A / g, 20A / g, 15A / g, 14A / g, 13A / g, and 12A / g. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0040] In order to better illustrate the present invention, further examples are given below.
[0041] Example 1
[0042] A method for preparing a composite electrode material:
[0043] Step 1: Cut the commercial nickel foam into small pieces of 5 cm×1 cm×1.6 mm, add them to acetone for ultrasonic treatment for 20 min, then use 3 mol / L dilute hydrochloric acid solution and deionized water for ultrasonic treatment for 15 min respectively, and dry them to obtain a nickel foam matrix;
[0044] Step 2: prepare a mixed aqueous solution of 10 mM zinc chloride and 0.5 M thiourea as a zinc sulfide electrodeposition solution; use nickel foam as an anode and a cathode, respectively, to perform electrodeposition in the zinc sulfide electrodeposition solution, with a deposition potential of -0.4 V to 1.3 V, a scan rate of 800 mV / s, and a deposition time of 20 min; wash and dry, and obtain a zinc sulfide / nickel foam electrode material at the negative electrode;
[0045] Step 3: prepare a mixed aqueous solution of 0.2 mM nickel chloride and 1 M thiourea as a nickel sulfide electrodeposition solution; use nickel foam as the anode and the above zinc sulfide / nickel foam electrode material as the cathode to perform electrodeposition in the nickel sulfide electrodeposition solution at a deposition potential of -0.4 V to 1.3 V, a scan rate of 800 mV / s, and a deposition time of 20 min. Wash and dry to obtain a nickel sulfide @ zinc sulfide / nickel foam composite electrode material at the negative electrode.
[0046] Figure 1This is the X-ray diffraction pattern of the nickel sulfide @ zinc sulfide / nickel foam composite electrode material prepared in this embodiment. Among them, the diffraction peaks of 21.7°, 37.8°, 38.3° and 44.4° belong to the (101), (003), (021) and (202) crystal planes of Ni3S2 (JCPDS no.44-1418), respectively. The diffraction peaks of 27.6°, 43.4°, 33.0° and 56.5° belong to the (003), (1,0,12), (102) and (1,0,10) crystal planes of ZnS (JCPDSno.44-1418), respectively. The diffraction peaks of 44.6° and 52.0° belong to the (111) and (200) crystal planes of nickel foam (CPDS no.12-0688J), respectively. This proves that the electrode material prepared in this embodiment is Ni3S2@ZnS / nickel foam composite electrode material.
[0047] Figure 2 This is a scanning electron microscope image of the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in this example, wherein Figure 2 (a) is the SEM image of blank nickel foam. Figure 2 (b) is the SEM image of zinc sulfide / nickel foam electrode material. Figure 2 (c) is the SEM image of nickel sulfide @ zinc sulfide / nickel foam composite electrode material. Figure 2 As can be seen in (b), zinc sulfide is coated on the nickel foam substrate in the form of thin flakes, the microscopic morphology of nickel sulfide is a cuboid or a cube, and the nickel sulfide nanomaterial uniformly coats zinc sulfide.
[0048] The nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in this embodiment was tested by XPS (X-ray electron spectroscopy analysis). Figure 3 The binding energies of 161.6 eV and 162.6 eV belong to S 3- 2p 1 / 2 and 2p 3 / 2 The binding energy of 168.7eV belongs to sulfur, which means that some sulfur ions are oxidized to sulfur in the air. The binding energies of 856.2eV and 874.1eV belong to Ni 2+ 2p 3 / 2 and 2p 1 / 2 The binding energies of 1022.1eV and 1045.2eV belong to Zn 2+ 2p 3 / 2 and Zn 2+ 2p 1 / 2 By analyzing the X-ray photoelectron spectrum, it is further proved that the material prepared in this embodiment is a Ni3S2@ZnS / nickel foam composite electrode material.
[0049] Example 2
[0050] A method for preparing a composite electrode material:
[0051] Step 1: Cut the commercial nickel foam into small pieces of 5 cm×1 cm×1.6 mm, add them to acetone for ultrasonic treatment for 20 min, then use 3 mol / L dilute hydrochloric acid solution and deionized water for ultrasonic treatment for 15 min respectively, and dry them to obtain a nickel foam matrix;
[0052] Step 2: prepare a mixed aqueous solution of 20 mM zinc chloride and 0.6 M thiourea as a zinc sulfide electrodeposition solution; use nickel foam as an anode and a cathode, respectively, to perform electrodeposition in the zinc sulfide electrodeposition solution, with a deposition potential of -0.4 V to 1.3 V, a scan rate of 820 mV / s, and a deposition time of 12 min; wash and dry, and obtain a zinc sulfide / nickel foam electrode material at the cathode;
[0053] Step 3: prepare a mixed aqueous solution of 0.4 mM nickel chloride and 1.3 M thiourea as a nickel sulfide electrodeposition solution; use nickel foam as the anode and the above zinc sulfide / nickel foam electrode material as the cathode to perform electrodeposition in the nickel sulfide electrodeposition solution at a deposition potential of -0.4 V to 1.3 V, a scan rate of 820 mV / s, and a deposition time of 12 min; wash and dry to obtain a nickel sulfide @ zinc sulfide / nickel foam composite electrode material at the cathode.
[0054] Example 3
[0055] A method for preparing a composite electrode material:
[0056] Step 1: Cut the commercial nickel foam into small pieces of 5 cm×1 cm×1.6 mm, add them to acetone for ultrasonic treatment for 20 min, then use 3 mol / L dilute hydrochloric acid solution and deionized water for ultrasonic treatment for 15 min respectively, and dry them to obtain a nickel foam matrix;
[0057] Step 2: prepare a mixed aqueous solution of 5 mM zinc chloride and 0.4 M thiourea as a zinc sulfide electrodeposition solution; use nickel foam as an anode and a cathode, respectively, to perform electrodeposition in the zinc sulfide electrodeposition solution, with a deposition potential of -0.4 V to 1.3 V, a scan rate of 780 mV / s, and a deposition time of 30 min, wash, dry, and obtain a zinc sulfide / nickel foam electrode material at the cathode;
[0058] Step 3: prepare a mixed aqueous solution of 0.1 mM nickel chloride and 0.7 M thiourea as a nickel sulfide electrodeposition solution; use nickel foam as the anode and the above zinc sulfide / nickel foam electrode material as the cathode to perform electrodeposition in the nickel sulfide electrodeposition solution at a deposition potential of -0.4 V to 1.3 V, a scan rate of 780 mV / s, and a deposition time of 30 min. Wash and dry to obtain a nickel sulfide @ zinc sulfide / nickel foam composite electrode material at the cathode.
[0059] Performance Testing
[0060] The nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 was placed in a 1M KOH electrolyte and tested for constant current charge and discharge curves at different mass current densities and different area current densities. Figure 4 and Figure 5 According to the constant current charge and discharge curve, the specific capacitance under different mass current density and different area current density is calculated, and the results are shown in Table 1 and Table 2.
[0061] Table 1 Specific capacitance at different mass current densities
[0062] <![CDATA[Mass current density (A·g -1 )]]> 19 20 21 22 23 24 25 <![CDATA[Specific mass capacitance (F·g -1 )]]> 1903.2 1813.3 1701.7 1628.0 1590.8 1536.7 1487.5
[0063] Table 2 Specific capacitance at different area current densities
[0064] <![CDATA[Areal current density (mA·cm -2 )]]> 5 6 7 8 9 10 20 <![CDATA[Areal specific capacitance (mF·cm -2 )]]> 401.7 371.0 351.2 332.0 318.0 315.0 153.3
[0065] It can be seen from the above table that the nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in the embodiment of the present invention has a higher specific capacity at different mass current densities and different area current densities.
[0066] The nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 was placed in 1M KOH electrolyte and tested for cyclic voltammetry at different scan rates (5mV / s, 20mV / s, 50mV / s, 100mV / s, 200mV / s, 500mV / s). A linear relationship diagram was drawn with the logarithmic values of the different scan rates log(v) as the abscissa and the logarithmic values of the corresponding currents log(i) at voltages of 0.2V and 0.4V as the ordinate. The results are shown in FIG. Figure 6 As shown. With log(i)=blog(v)+loga, when the slope b of the straight line is 0.5, the chemical reaction on the surface of the surface electrode is a surface-controlled process, and when the slope b of the straight line is 1.0, it indicates that the chemical reaction process on the surface of the electrode is a diffusion-controlled process. After fitting, the slopes of the two straight lines of the composite electrode material of Example 1 at 0.2V and 0.4V are both 0.5, proving that the chemical reaction on the electrode surface at 0.2V and 0.4V is a surface-controlled process.
[0067] The corresponding current at 0.4V voltage and different scan rates are calculated according to i / v 0.5 =k1v 0.5 +k2 equation is plotted, and k1v is obtained based on the slope and intercept of the fitting graph 0.5 and k2 value. k1v 0.5 represents surface control, k2 represents diffusion control, and the proportion of surface control = k1v 0.5 / (k1v 0.5+k2)*100%, the proportion of diffusion control = k2 / (k1v 0.5 + k2)*100%. The calculated result is as follows Figure 7 As shown. Figure 7 It can be intuitively seen whether the electrochemical reaction on the electrode surface is mainly diffusion controlled or mainly surface controlled at different scan rates.
[0068] The nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 was tested for its resistance value using a four-point probe technique, and the resistivities measured in three different directions were 8.84 mΩ·mm, 9.45 mΩ·mm, and 10.07 mΩ·mm, respectively.
[0069] The nickel sulfide@zinc sulfide / nickel foam composite electrode material prepared in Example 1 was tested for cycle retention rate in 1M KOH electrolyte. The results are as follows: Figure 8 As shown in the figure, it can be seen that the capacity retention rate of the nickel sulfide @ zinc sulfide / nickel foam composite electrode material prepared in the embodiment of the present invention after 500 cycles is 81.4%, the capacity retention rate after 1000 cycles is 71.7%, the capacity retention rate after 1500 cycles is 64.1%, the capacity retention rate after 2000 cycles is 59.3%, the capacity retention rate after 2500 cycles is 56.1%, the capacity retention rate after 3000 cycles is 53.8%, the capacity retention rate after 3500 cycles is 52.9%, the capacity retention rate after 4000 cycles is 52.4%, the capacity retention rate after 4500 cycles is 52.0%, and the capacity retention rate after 5000 cycles is 51.6%. It proves that the nickel sulfide @ zinc sulfide / nickel foam composite electrode material prepared in the embodiment of the present invention has good cycle performance.
[0070] The composite electrode materials prepared in Examples 2-3 can achieve substantially the same effect as that in Example 1.
[0071] Comparative Example 1
[0072] This comparative example provides a method for preparing a composite electrode material, which is exactly the same as the method in Example 1, except that the scanning rate of the electrodeposition of zinc sulfide in step 2 is 50 mV / s, and the remaining steps and parameters are the same.
[0073] The SEM image of the zinc sulfide / nickel foam electrode material prepared in this comparative example is as follows Fig. 9 As shown in the figure, it can be seen that after changing the deposition scanning rate of zinc sulfide, zinc sulfide grows upright on the surface of nickel foam and cannot form a lamellar coating structure.
[0074] The nickel sulfide / zinc sulfide / nickel foam composite electrode material prepared in this comparative example was tested in 0.1M KOH electrolyte for constant current charge-discharge curves at different mass current densities. The results are as follows: Fig.10 As shown, the specific capacitance at different mass current densities was calculated based on the constant current charge and discharge curves, and the results are shown in Table 3.
[0075] Table 3 Specific capacitance at different mass current densities
[0076] <![CDATA[Mass current density (A·g -1 )]]> 12 13 14 15 20 60 <![CDATA[Specific mass capacitance (F·g -1 )]]> 808.0 788.7 770.1 740.0 700.0 250.0
[0077] Comparative Example 2
[0078] This comparative example provides a method for preparing a composite electrode material, and the specific steps are as follows:
[0079] Step 1: Cut the commercial nickel foam into small pieces of 5 cm×1 cm×5 mm, add them to acetone for ultrasonic treatment for 20 min, then use 3 mol / L dilute hydrochloric acid solution and deionized water for ultrasonic treatment for 15 min respectively, and dry them to obtain a nickel foam matrix;
[0080] Step 2: prepare a mixed aqueous solution of 0.2 mM nickel chloride and 1 M thiourea as a nickel sulfide electrodeposition solution; use nickel foam as an anode and the zinc sulfide / nickel foam electrode material as a cathode to perform electrodeposition in the nickel sulfide electrodeposition solution at a deposition potential of -0.4 V to 1.3 V, a scan rate of 800 mV / s, and a deposition time of 20 min; wash and dry to obtain a nickel sulfide / nickel foam electrode material at the cathode;
[0081] Step 3: prepare a mixed aqueous solution of 10 mM zinc chloride and 0.5 M thiourea as a zinc sulfide electrodeposition solution; use nickel foam as an anode and a cathode, respectively, to perform electrodeposition in the zinc sulfide electrodeposition solution, with a deposition potential of -0.4 V to 1.3 V, a scan rate of 800 mV / s, and a deposition time of 20 min; wash and dry to obtain a zinc sulfide / nickel sulfide / nickel foam composite electrode material at the cathode.
[0082] The zinc sulfide / nickel sulfide / nickel foam composite electrode material prepared in this comparative example was tested for constant current charge-discharge curves at different area current densities in 0.1M KOH electrolyte. The results are as follows: Fig.11 As shown, the specific capacitance at different area current densities was calculated based on the constant current charge and discharge curves, and the results are shown in Table 4.
[0083] Table 4 Specific capacitance of the composite electrode materials prepared in Example 1 and Comparative Example 2 at different area current densities
[0084]
[0085] Comparative Example 3
[0086] This comparative example provides a method for preparing a composite electrode material, and the specific steps are as follows:
[0087] Step 1: Cut the commercial nickel foam into small pieces of 5 cm×1 cm×5 mm, add them to acetone for ultrasonic treatment for 20 min, then use 3 mol / L dilute hydrochloric acid solution and deionized water for ultrasonic treatment for 15 min respectively, and dry them to obtain a nickel foam matrix;
[0088] Step 2: prepare a mixed aqueous solution of 0.2 mM nickel chloride and 1 M thiourea as a nickel sulfide electrodeposition solution; use nickel foam as an anode and the zinc sulfide / nickel foam electrode material as a cathode to perform electrodeposition in the nickel sulfide electrodeposition solution at a deposition potential of -0.4 V to 1.3 V, a scan rate of 800 mV / s, and a deposition time of 20 min; wash and dry to obtain a nickel sulfide / nickel foam electrode material at the cathode;
[0089] Step 3: prepare a mixed aqueous solution of 10 mM zinc chloride and 0.5 M thiourea as a zinc sulfide electrodeposition solution; use nickel foam as the anode and cathode, respectively, and perform electrodeposition in the zinc sulfide electrodeposition solution at a deposition potential of -0.4 V to 1.3 V, a scan rate of 50 mV / s, and a deposition time of 20 min. Wash and dry to obtain a zinc sulfide / nickel sulfide / nickel foam composite electrode material at the cathode.
[0090] The SEM image of the zinc sulfide / nickel sulfide / nickel foam composite electrode material prepared in this comparative example is as follows: Fig.12 As shown in the figure, it can be seen that no double-shell structure is formed.
[0091] The zinc sulfide / nickel sulfide / nickel foam composite electrode material prepared in this comparative example was tested for constant current charge-discharge curves at different mass current densities in 0.1M KOH electrolyte. The results are as follows: Fig.13 As shown, the specific capacitance at different mass current densities was calculated based on the constant current charge and discharge curves, and the results are shown in Table 5.
[0092] Table 5 Specific capacitance at different mass current densities
[0093] <![CDATA[Mass current density (A·g -1 )]]> 12 13 14 15 20 60 <![CDATA[Specific mass capacitance (F·g -1 )]]> 996.0 942.5 923.7 912.5 903.3 600.0
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite electrode material, characterized in that: The steps include: Step a, using nickel foam as an anode and a cathode, respectively, to perform electrodeposition in a zinc sulfide electrodeposition solution, washing, and drying to obtain a zinc sulfide / nickel foam electrode material; wherein the deposition potential is -0.4V to 1.3V, and the scanning rate is 780mV / s to 820mV / s; the zinc sulfide electrodeposition solution is a mixed aqueous solution of a soluble zinc salt and thiourea, wherein the concentration of the soluble zinc salt is 5mmol / L to 20mmol / L, and the concentration of the thiourea is 0.4mol / L to 0.6mol / L; Step b, using nickel foam as an anode and the zinc sulfide / nickel foam electrode material as a cathode, performing electrodeposition in a nickel sulfide electrodeposition solution, washing, and drying to obtain a nickel sulfide@zinc sulfide / nickel foam composite electrode material; wherein the deposition potential is -0.4V to 1.3V, and the scanning rate is 780mV / s to 820mV / s; the nickel sulfide electrodeposition solution is a mixed aqueous solution of a soluble nickel salt and thiourea, wherein the concentration of the soluble nickel salt is 0.1mmol / L to 0.4mmol / L, and the concentration of the thiourea is 0.7mol / L to 1.3mol / L; In step a and step b, the electrodeposition time is 12 min to 30 min.
2. The method for preparing a composite electrode material according to claim 1, characterized in that: The soluble zinc salt is zinc chloride or zinc nitrate.
3. The method for preparing a composite electrode material according to claim 1, characterized in that: The soluble nickel salt is nickel chloride or nickel nitrate.
4. A composite electrode material, characterized in that: The composite electrode material is prepared by the preparation method of the composite electrode material according to any one of claims 1 to 3.
5. A positive electrode, characterized in that Comprising the composite electrode material as claimed in claim 4.
6. A supercapacitor, characterized in that: Comprising the positive electrode as claimed in claim 5.
Citation Information
Patent Citations
Preparation method of supercapacitor composite electrode material based on foamed nickel
CN108597893A
Supercapacitor and production method thereof
CN109326456A